The Effect Of Financial Literacy And Government Support On The Sustainability Of Msmes In Bengkulu City - Yolanda, Dwi; Made E.G., Ida Ayu; Harwini, Dewi (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the influence of financial literacy and government support on the sustainability of MSMEs in Bengkulu City. The research method used is a quantitative approach with an associative type of research. Data were collected through questionnaires distributed to MSME actors in Bengkulu City. The sampling technique used was purposive sampling, while the data were analyzed using simple linear regression analysis with the help of SPSS software to examine the effect of the financial literacy variable (X) on MSME financial management (Y). Based on the results of the research and data analysis conducted, it can be concluded that financial literacy and government support influence the sustainability of MSMEs in the Bengkulu City community. Partially, financial literacy (X1) has a significant effect on MSME sustainability, while government support (X2) does not have a significant effect. Simultaneously, both variables have a significant influence on MSME sustainability with a contribution of 65%. The regression equation obtained is Y = 20.447 + 0.386X1 + 0.190X2, indicating that an increase in financial literacy and government support tends to enhance the sustainability of MSMEs in Bengkulu City.